Paradigma Perkembangan Akuntansi Terimplikasi Dalam Nilai-Nilai Islam - Muhammad Fadhil Junery (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2016)
The limitations of the human mind and also the various interests which always refers to the mundane aspects, then all rules in the order of economic and business cannot be released granted to man to design these rules without any ropes of restraint as a means to restrict people from doing arbitrary and more likely just as homo economicus, which is why Islam was present to bring the values ​​of truth and justice which serve as guidance for not only humans as homo economicus but also as homo and homo religious ethicus. Seeing some of the weaknesses and limitations of today's accounting in its development, mengaharuskan Muslims to meleraikan creasing these problems, by making the sharia as a paradigm in building a conceptual framework of accounting that can be used as a foothold in the development of accounting format is more appropriate. And foster the values ​​of the essence in the accounting value of responsible, fair and true.